O crédito imobiliário no Brasil e sua relaç\~ao com a política monetária - Mário Jorge Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– Switching model, we estimate the demand for mortgage using aggregate monthly data from January 2003 to September 2012. The results show that this variable has been subject to cycles of contraction and expansion since 2003. The boom starts at the end of 2005 is marked by the alternation of two distinct regimes. The first one that concentrates between late 2005 until early 2009 seems to be driven by factors pro-market resulting from changes in legislation, economic growth, rising in real income, etc. The situation changes at the beginning of 2009 when the condition of the demand for mortgage is mainly motivated by countercyclical measures adopted by the federal government with the aim of mitigating the effects of the world economic crisis of 2007-2008. The recessive phase of the credit cycle is linked to a single regime that extends until 2005 returning around March 2012 when the series of credit seems to slow down. We also applied the structural VAR model with the purpose of evaluating the effect of a monetary policy shock on the demand mortgage. According to the results, a contractionary shock produces a negative effect on real estate. We note a continuous and sharp decline in mortgage demand, price home, industrial output construction as well as a rising on defaults.
Keywords: E32; R38; 330; mortgage choice; reverse causality; Markov Switching model; structural VAR; directed acyclic graph